Structural Analysis of Interactions between Epidermal Growth Factor Receptor (EGFR) Mutants and Their Inhibitors - Yingzhe Guo; Zeqian Du; Ting Shi (Biophysica, 2023)
People’s lives and health are gravely threatened by non-small-cell lung cancer (NSCLC). Mutations in epidermal growth factor receptor (EGFR), a transmembrane receptor tyrosine kinase, are considered one of the causes of NSCLC. Tyrosine kinase inhibitors (TKIs) are typically used to treat patients with EGFR mutations. In this study, Gefitinib, a member of the first generation of TKIs, was used to treat an EGFR single-point mutation (single mutant, SM). Patients harboring additional T790M mutations in the kinase domain of the EGFR were resistant to Gefitinib. Then, the L858R/T790M double mutation (double mutant, DM) was treated with the second generation of TKIs, such as Afatinib. Here, we constructed four computational models to uncover the structural basis between EGFR mutants (SM and DM) and corresponding inhibitors (Gefitinib and Afatinib). The binding energy in the G-SM (representing Gefitinib in complex with SM) system was larger than that in the G-DM (Representing Gefitinib in complex with DM) system. Gefitinib’s affinity with L792 and M793 was drastically reduced by the longer side chain of M790 in the G-DM system, which pushed Gefitinib outside of the pocket. Additionally, the A-DM system’s binding energy was higher than the G-DM system’s. Afatinib, unlike Gefitinib, induced the P-loop region to move downwards to decrease the pocket entrance size to accommodate Afatinib properly and stably in the A-DM (Afatinib in complex with DM) system. These results uncover the details of interactions between EGFR and its inhibitors and shed light on the design of new tyrosine kinase inhibitors.